(untitled) (African Journal of Biomedical Research, 2020)
Tuberculosis (TB) has remained the leading cause of morbidity and mortality among people living with HIV (PLHIV). Nigeria has the highest incidence of TB/HIV co infection and HIV associated TB deaths in sub Saharan Africa. Therefore TB prevention among PLHIV is of utmost necessity. We assessed tuberculosis intensified case finding (ICF) cascade and isoniazid preventive therapy (IPT) for people living with HIV in heath care facilities in Enugu State, Nigeria. It was a cross sectional study conducted between February and May, 2019. We reviewed a total of 993 folders of PLHIV of PLHIV in the nine health care facilities offering ART in the State. Data was collected with ICF data collection form adapted from literature. Percentages were used to analyse data and their values compared using chi square statistics. Ninety eight point eight per cent of PLHIV had their TB screen done and documented as at last visit to the clinic, 80% of those screened positive had documented TB diagnostic evaluation while 96.2% of PLHIV with positive TB evaluation were placed on anti-TB treatment. Furthermore, 61.2 % of PLHIV had ever received a course of IPT. Significant differences were observed in TB screening by location and IPT administration by type of health care facility (p<.05). Shortage of staff and poor remuneration were the most reported factors affecting implementation. The gaps identified in the implementation of ICF cascade and IPT have implications for public health and education. To reduce TB burden among PLHIV, all stakeholders must be involved in TB/HIV activities.